Critical thinking instruction and technology enhanced learning from the student perspective: A mixed methods research study - Swart, Ruth (Nurse education in practice, 2017)
Critical thinking is acclaimed as a valuable asset for graduates from higher education programs. Technology has advanced in quantity and quality; recognized as a requirement of 21st century learners. A mixed methods research study was undertaken, examining undergraduate nursing student engagement with critical thinking instruction, platformed on two technology-enhanced learning environments: a classroom response system face-to-face in-class and an online discussion forum out-of-class. The Community of Inquiry framed the study capturing constructivist collaborative inquiry to support learning, and facilitate critical thinking capability. Inclusion of quantitative and qualitative data sources aimed to gather a comprehensive understanding of students' development of critical thinking and engagement with technology-enhanced learning. The findings from the students' perspectives were positive toward the inclusion of technology-enhanced learning, and use in supporting their development of critical thinking. Students considered the use of two forms of technology beneficial in meeting different needs and preferences, offering varied means to actively participate in learning. They valued critical thinking instruction being intentionally aligned with subject-specific content facilitating understanding, application, and relevance of course material. While the findings are limited to student participants, the instructional strategies and technology-enhanced learning identified as beneficial can inform course design for the development of critical thinking. •Intentional integration of explicit critical thinking instruction and technology aligned with professional knowledge to support critical thinking.•Online discussion questions personalizing learning and relating content to real practice situations promote reflection and critical thinking.•Questions which instigate discussion and stimulate awareness of diverse perspectives are useful in developing critical thinking.